Penggunaan Platform Merdeka Mengajar oleh Guru SMA Negeri 1 Lembang Jaya - Lidya Elviana; Gustia Sainanda; Merika Setiawati (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
The background of this research is the development of teacher quality and quality which must be adapted to the times so that it is developed in the world of education. The independent teaching platform is used to assist teachers in preparing learning materials. The purpose of this research is to see how teachers use the independent teaching platform at SMA Negeri 1 Lembang Jaya. The method used in this research is descriptive qualitative. The results of this study indicate that the independent teaching platform has a display that is easy to understand and easy to access. The available features are in the form of student assessments, tools, self-training, community, proof of work, inspirational videos. The teaching tools provided still need to be developed so that they can be used more optimally in creating works for both teachers and students. The benefits of using the independent teaching platform can be felt reciprocally by teachers and students. So it can be concluded that the use of this independent teaching platform can improve the quality, skills, creativity and potential of each teacher.